Simultaneous determination of a novel oral Janus kinase inhibitor ASP015K and its sulfated metabolite in rat plasma using LC‐MS/MS. (7th November 2014) - Oda, Kazuo; Mera, Katsumi; Nagasaka, Yasuhisa; Tokoro, Kazumi
Abstract A sensitive and selective liquid chromatography with tandem mass spectrometry (LC‐MS/MS) was developed for determining the concentrations of novel Janus kinase inhibitor ASP015K and its sulfated metabolite M2 in rat plasma. This method involves solid‐phase extraction (SPE) from 25 μL of rat plasma. LC separation was performed on an Inertsil PH‐3 column (100 mm L ×4.6 mm I.D., 5 µm) with a mobile phase consisting of 10 mM ammonium acetate and methanol under linear gradient conditions. Analytes were introduced to the LC‐MS/MS through an electrospray ionization source and detected in positive‐ion mode using selected reaction monitoring. Standard curves were linear from 0.25 to 500 ng/mL (r ≥0.9964). This assay enabled quantification of ASP015K and M2 at a concentration as low as 0.25 ng/mL in rat plasma. Validation data demonstrated that the method is selective, sensitive and accurate. Further, we also successfully applied this method to a preclinical pharmacokinetic study in rats. Copyright © 2014 John Wiley & Sons, Ltd.